Analisa Kekerasan Dengan Pengujian Vickers Pada Wood Polymer Composite Menggunakan Metode Hot Press - Pranata, Hadi; Aldori, Yopan Rahmad; Handoko, Ari (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
Wood Polymer Composite (WPC) is a composite material composed of wood powder and recycled plastic. This material has been widely developed as an environmentally friendly alternative since it combines the natural properties of wood with the advantages of polymers. The manufacturing process involves mixing wood powder and plastic, followed by heating and molding into various structural forms. WPC exhibits high strength, durability, and resistance to environmental conditions, making it a popular alternative to solid wood. A typical composition consists of 50% wood powder and 50% high-density polyethylene (HDPE). In addition to improving wood utilization efficiency, WPC also contributes to reducing plastic waste accumulation that is difficult to decompose in the environment.